Comparison of Clinical Presentation and Surgical Outcomes Between Recurrent Acute Rhinosinusitis and Chronic Rhinosinusitis. (November 2018) - Sohn, Hyun Gi; Park, Seung Jin; Ryu, In Sun; Lim, Hyun Woo; Song, Yong Jin; Yeo, Nam-Kyung
Introduction: The authors assessed clinical presentations and anatomic variants among patients with recurrent acute rhinosinusitis (RARS), chronic rhinosinusitis (CRS) without nasal polyps (CRSsNP), and CRS with nasal polyps (CRSwNP). Additionally, differences in the postoperative improvement of each category were evaluated. Methods: The authors performed an analysis of 304 patients who underwent endoscopic sinus surgery. They were divided into groups with RARS, CRSsNP, and CRSwNP. Patients had to complete the Sino-Nasal Outcome Test (SNOT-20) on surgery 1 day before and 6 months after surgery. Patient demographics and comorbidities were reviewed. We reviewed all patients' computed tomographic findings to analyze anatomic variants. Results: No significant differences were found among the average preoperative SNOT-20 scores of the 3 groups. Patients with RARS were significantly more likely to show agger nasi cells, Haller cells, and septal deviation on computed tomography. Those with CRSwNP had significantly smaller mean infundibular widths. All groups showed significantly improved SNOT-20 scores postoperatively. Conclusion: The different anatomic variants found among patients with RARS, CRSsNP, and CRSwNP can facilitate surgical prognostic evaluation.